2015
DOI: 10.1111/bph.13114
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting endocannabinoid biosynthesis: a novel approach to the treatment of constipation

Abstract: BACKGROUND AND PURPOSEEndocannabinoids are a family of lipid mediators involved in the regulation of gastrointestinal (GI) motility. The expression, localization and function of their biosynthetic enzymes in the GI tract are not well understood. Here, we examined the expression, localization and function of the enzyme diacylglycerol lipase-α (DAGLα), which is involved in biosynthesis of the endocannabinoid 2-arachidonoylglycerol (2-AG). EXPERIMENTAL APPROACHCannabinoid CB1 receptor-deficient, wild-type control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…Animal studies demonstrated the regulation of oleamide by MZRW possibly through augmentation of FAAH-mediated degradation. Bashashati et al proposed that inhibiting endocannabinoid biosynthesis could be a novel approach for constipation treatment, which has been validated by animal studies (Bashashati et al, 2012;Bashashati et al, 2015). Very interestingly, our findings suggest a novel FC treatment approach: enhancing endocannabinoid degradation by promoting the expression/activity of intestinal FAAH.…”
Section: Discussionsupporting
confidence: 67%
“…Animal studies demonstrated the regulation of oleamide by MZRW possibly through augmentation of FAAH-mediated degradation. Bashashati et al proposed that inhibiting endocannabinoid biosynthesis could be a novel approach for constipation treatment, which has been validated by animal studies (Bashashati et al, 2012;Bashashati et al, 2015). Very interestingly, our findings suggest a novel FC treatment approach: enhancing endocannabinoid degradation by promoting the expression/activity of intestinal FAAH.…”
Section: Discussionsupporting
confidence: 67%
“…Proof of concept for this idea come from studies using DAGL and FAAH inhibitors. Inhibitors of DAGL have been examined in models of constipation; they effectively normalized slowed transit in opioid-induced constipation and in congenital slow-transit constipation 90 . Conversely, inhibiting the degradation of endocannabinoids, by blocking FAAH, has antidiarrheal and anti-nociceptive effects in models of accelerated motility and in mice with oil of mustard-induced colitis, respectively 91, 92 .…”
Section: Cannabinoids and Control Of Gi Motilitymentioning
confidence: 99%
“…Indeed, studies already have addressed the endocannabinoids in the treatment of constipation. Bashahati et al [36] found that by inhibiting diacylglycerol lipase-α, enzyme involved in biosynthesis of 2-AG, fecal output in genetically constipated mouse strain is normalized.…”
Section: Discussionmentioning
confidence: 99%